2006
DOI: 10.1159/000094543
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Semantic Fluency as an Additional Screening Tool for Subjects with Questionable Dementia

Abstract: Background: Subjective memory complaints in subjects with mild cognitive impairment may represent a genuine decline in episodic memory. This paper evaluates the neuropsychological correlates of the semantic fluency test in subjects with questionable dementia (QD). Methods: A total of 331 Chinese subjects (118 normal controls, NC, 150 with QD and 63 with mild Alzheimer’s disease, AD) were assessed with the Category Verbal Fluency Test (CVFT), the AD Assessment Scale – cognitive subscale (ADAS-Cog), and digit an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 40 publications
1
43
0
3
Order By: Relevance
“…Other studies have demonstrated that decreases in semantic fluency performance (e.g. animal naming) may be indicative of single-domain aMCI [12,13,14,15]. Some of these studies also found statistically significant decreases in letter fluency performance among those categorized as single-domain aMCI [9,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have demonstrated that decreases in semantic fluency performance (e.g. animal naming) may be indicative of single-domain aMCI [12,13,14,15]. Some of these studies also found statistically significant decreases in letter fluency performance among those categorized as single-domain aMCI [9,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Além disso, deve-se considerar que processos complexos como o reconhecimento de faces, o processamento emocional, o raciocínio sequencial e a fluência verbal por dependerem da memória semântica podem estar comprometidos nessa síndrome (JEFFERIES; PATTERSON; RALPH, 2006). Embora a memória episódica possa estar relativamente preservada (especialmente para material visual), sendo usada como suporte para reaprendizagem do conhecimento sobre palavras e objetos, artigos recentes também têm constatado déficits nessa área (TU et al, 2013;LAM et al, 2006;CAIXETA;MANSUR, 2005). Um estudo de Honolulu identificou sujeitos com queixas subjetivas de memória, déficits na memória episódica e fluência verbal três anos antes do estabelecimento clínico da DS (LAM et al, 2006).…”
Section: Discussionunclassified
“…Embora a memória episódica possa estar relativamente preservada (especialmente para material visual), sendo usada como suporte para reaprendizagem do conhecimento sobre palavras e objetos, artigos recentes também têm constatado déficits nessa área (TU et al, 2013;LAM et al, 2006;CAIXETA;MANSUR, 2005). Um estudo de Honolulu identificou sujeitos com queixas subjetivas de memória, déficits na memória episódica e fluência verbal três anos antes do estabelecimento clínico da DS (LAM et al, 2006). Na variante comportamental, contrariamente à noção popular de que a memória episódica estaria preservada, pesquisas têm encontrado prejuízo na codificação e consolidação de informações em estágios iniciais da doença (XIE et al, 2010;MATUSZEWSKI et al, 2006).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…70,71 Thus, the CDR 0.5 group is well placed for use in studies that seek to examine intermediate states between normal aging and dementia, such as MCI (table 2). 72 Available studies in Asian populations add to the growing body of evidence in Caucasian populations that the CDR 0.5 group is similar to very mild Alzheimer's disease with regards to cognitive features, 35,61,73 behavior, 67 psychometric performance, 72,74,75 and longitudinal progression, 35,37,76 as well as structural and functional neuroimaging characteristics. 41,42 Many of these studies utilize a more liberal definition of MCI that equates to CDR 0.5, although some studies subclassify the CDR 0.5 group into MCI not demented (corresponding to CDR 0.5 uncertain dementia) and MCI incipient dementia (equivalent to CDR 0.5 incipient or very mild dementia).…”
Section: Evidence Of Cdr Use In Asian Populations Validation Studiesmentioning
confidence: 96%